Capital account liberation : methods and applications - Yirong, Ying; Forrest, Jeffrey Yi-Lin, 1959- (Systems evaluation, prediction, and decision-making series., 2015)
Along with the development of economic globalization, many countries have begun to relax their controls on their capital accounts. However, the recent financial crises in Latin American countries as well as the exchange rate crises in Southeast Asian countries have shown that there is major risk associated with capital account liberalization. This book details the benefits and risks of capital account liberalization and explains how to take an open-door policy at the appropriate time in order to reduce the risk to the lowest possible level. Supplying a complete mathematical analysis framework f.